Answer:
y=sin(ln(x))
Step-by-step explanation:
First, we have to order the terms as follows and express y' as dy / dx:
[tex]x*\frac{dy}{dx} =\sqrt{(1-y^{2} )} \\\frac{x}{dx}=\frac{dy}\sqrt{(1-y^{2} )}}\\\frac{dx}{x}=\frac{dy}{\sqrt{(1-y^{2} )} }[/tex]
Then, we have to integrate
[tex]\int{\frac{dx}{x}=\int{\frac{dy}{\sqrt{(1-y^{2} )} }[/tex]
with this solution after integration:
[tex]ln(x)+C1=arcsin(y)+C2[/tex]
Then, we have to reorder
[tex]arcsin(y)=ln(x)+C[/tex]
and applied Sin function on both sides
[tex]sin(arcsin(y))=sin(ln(x)+C)\\y=sin(ln(x)+C)[/tex]
To define the value of C, we use the known point y(1)=0 and replace in the equation
[tex]y=sin(ln(x)+C)\\0=sin(ln(1)+C)\\0=sin(0+C)\\0=sin(C)\\C=arcsin(0)\\C=0[/tex]
The function that proves that differential equation is
[tex]y=sin(ln(x))[/tex]